Syndicated lending : practice and documentation - Rhodes, Tony.; Campbell, Mark; Weaver, Christoph; Bailey, Andrew; Andrews, Cameron (London : Euromoney Books, 2004)
The book provides practical explanations by borrowers and bankers of how to arrange, lead and manage a syndicated loan and includes an up-to-date discussion of documentary issues using annotated documents. This book allows you to benefit from decades of combined syndicated lending expertise. The book is a complete guide, taking the reader through the various stages of syndicated lending from the opening phase of seeking a mandate through to syndicating, documenting and the closing of a transaction. Stay up to date with the changes in the syndication market.
Includes index
Includes index
lje 13/07/16, ijb 11/03/2019
Loans
Keywords: Bank loans; Syndicates (Finance); Syndicated lending; Roll-over credits